Suppression of tryptophan synthase activates cotton immunity by triggering cell death via promoting SA synthesis. (21st February 2019) - Miao, Yuhuan; Xu, Lian; He, Xin; Zhang, Lin; Shaban, Muhammad; Zhang, Xianlong; Zhu, Longfu
Summary: Primary metabolism plays an important role in plant growth and development, however the relationship between primary metabolism and the adaptive immune response is largely unknown. Here, we employed RNA interference (RNAi), virus‐induced gene silencing (VIGS) technology, phytohormone profiling, genetic studies, and transcriptome and metabolome analysis to investigate the function of the tryptophan synthesis pathway in the resistance of cotton to V. dahliae . We found that knock‐down of GbTSA1 (Tryptophan Synthase α) and GbTSB1 (tryptophan synthase β) induced a spontaneous cell death phenotype in a salicylic acid (SA)‐dependent manner and enhanced resistance to V. dahliae in cotton plants. Metabolome analysis showed that indole and indolic metabolites were highly accumulated in GbTSA1 ‐ or GbTSB1 ‐silenced plants. Transcriptomic analysis showed that exogenous indole promotes the expression levels of genes involved in SA synthesis and the defense response. Similarly, indole application strongly enhanced cotton resistance to V. dahliae . These results suggested that metabolic intermediates in the Trp synthesis pathway may be a signal to activate SA synthesis. These results also provided a strategy to elicit plant defense responses by the application of indole. Significance Statement: Our study reveals that the metabolic intermediates in the Trp synthesis pathway could be a signal to active SA synthesis. Moreover, indole has the potential as an environmentally friendly elicitor in plant protection against soil‐borne pathogens, through drop irrigation.